Ecobiological aspects of invasive apple snails (Pomacea spp.) in rice fields, Peninsular Malaysia - Ahmed, Gilal Arfan (2015)
Alien invasive apple snails, Pomacea canaliculata Lamarck and Pomacea maculata Perry were introduced into Malaysia around 1991. Since their introduction, Pomacea spp. have damaged vast area under rice cultivation and are major threat to rice self sufficiency in Malaysia. However, no thorough research has been done on their ecobiological aspects in the country, especially in Peninsular Malaysia. Therefore, this study focused on understanding the different ecobiological aspects of these apple snails. Studies on the abundance of Pomacea spp. in twenty five rice fields of five states in Peninsular Malaysia, confirmed the presence of P. maculata and P. canaliculata. Pomacea maculata was more abundant and widely distributed. Population of P. canaliculata was not recorded in Penang. Rice fields in Perak showed the highest population of snails (10.13 snails / m2). The lowest population was recorded from rice fields of Kelantan and Kedah during sowing and harvesting, respectively. Population of snails was significantly higher during sowing of rice as compared to harvesting due to the presence of plenty of water and young rice seedlings as their food. Population fluctuation of egg, juvenile and adult snails in a rice field over two rice growing seasons from August, 2013 to May, 2014 highlighted comparatively higher populations during off season in comparison to main season. Population of different stages of P. maculata increased during reproductive and ripening stages of rice. No population of juveniles, females and males was recorded at harvesting due to water drain out from rice field. Higher populations were significantly correlated to relative humidity, rainfall, and density of Limnocharis flava and Ischaemum rugosum. Different indices of population dispersion i.e., variance to mean ratio, Lloyd index and Green Co-efficient mostly confirmed regular or uniform dispersion pattern of various stages of P. maculata. However, Iwao’s patchiness regression and Taylor’s power law mostly confirmed aggregated dispersion pattern. Findings of the growth studies confirmed that size of one day hatchlings of P. canaliculata was significantly higher than P. maculata. Comparatively higher growth rate was observed in P. canaliculata than P. maculata with both species sexually matured during 27th and 32nd weeks, respectively. No significant difference was observed in shell length, height and width of the two species at maturity. Both Pomacea spp. started consuming rice during 4th week after hatching from eggs. Mating and oviposition behavior studies confirmed higher mating frequency, oviposition duration and higher number of eggs per clutch of smaller size along with more eggs per minute in P. maculata. Mating and oviposition in both species occurred mostly during the night hours. No difference was recorded for mating duration, oviposition frequency, hatching success and hatching period between two species. Highly significant correlation between oviposition duration and total number of eggs was only observed in P. canaliculata. Feeding preference of 1, 2 and 3 cm sized snails of the two species on leaves and stems of rice and L. flava confirmed higher preference for L. flava in all three sizes based on higher consumption. Limnocharis flava also supported higher growth and weight gain in both Pomacea spp. Rice stems supported the least growth and weight gain. Study on damage potential of two Pomacea spp. to rice established by direct seeding and 14, 21 and 28 days old transplanted seedlings showed that both species caused 100% loss to direct seeded and 14 days transplanted rice. Damage decreased with older transplanted seedlings with the least damage recorded in 28 days old transplanted rice. No loss of seedlings by two Pomacea spp. was recorded in 21 and 28 days old transplanted rice after 5th and 4th weeks, respectively. Sowing methods and damage by Pomacea spp. caused considerable reduction in number of tillers, panicles and Leaf Area Index. Higher number of these parameters was recorded in 21 days old transplanted rice control treatment. Additional space in 28 days old transplanted rice snail infested plots due to missing seedlings compensated them by producing more spikelets per panicle, grain filling percentage and grain harvest index. Accordingly, yields in 28 days old transplanted rice treatments damaged by Pomacea spp. were comparable with control treatments of 28 and 21 days old transplanted rice. Studies on the effect of water levels of 5 and 2 cm, and densities of 1, 2 and 3 snails per plot of Pomacea spp. confirmed significantly higher damage by all the snail densities at 5 cm water level. Higher damage was recorded at a density of 3 snails / plot of either species. No significant difference between P. maculata and P. canaliculata was recorded in rice grown by different methods at two water levels, suggesting the same damage potential of the two species to rice.